Efektivitas Konseling Individual dalam Meningkatkan Kepercayaan Diri Siswa pada Pembelajaran di Sekolah Dasar - Mujahadah Mujahadah; Patimah Azahra; Rina Hayati (PT. Global Pustaka Ilmiah, 2026)
This study aims to boost students’ self-confidence through an individual counseling approach at Murung Sari 5 Elementary School in Amuntai. Low self-confidence among students can hinder their academic and social development. Therefore, individual counseling interventions are expected to serve as a solution to improve this psychological aspect. This study was conducted over three cycles of meetings, each consisting of individual counseling sessions tailored to the students’ needs and characteristics. Each cycle included problem identification, intervention delivery, as well as evaluation and reflection to assess the students’ progress in self-confidence. The results of this study indicate a significant increase in students’ self-confidence, reflected in their ability to interact better with peers, express their opinions, and face challenges in the classroom with greater confidence. Overall, the individual counseling approach proved effective in enhancing the self-confidence of students at Murung Sari 5 Elementary School in Amuntai, which is expected to contribute to their overall psychosocial development.